Water resistant starch xanthide filled natural rubber - Chuoy-Plong P; Hepburn C (Indian Journal of Natural Rubber Research, 1993)
Starch xanthide-natural rubber latex masterbatching process was studied starting from both latex concentrate and fresh field latex. Masterbatches of varying starch xanthide content were prepared. Physical properties of the compounds containing various starch xanthide loading were investigated both before and after exposure to water. The use of mercapto silane (Silane A 189) coupling agent in starch xanthide filled natural rubber was examined with the intention of reducing its water sensitivity. It was concluded that vulcanizates containing Silane A 189 have significantly improved physical properties in both dry and wet states and have substantially lower water sensitivity.
Keywords: Coupling agent; Natural rubber; Reinforcement; Silane; Starch xanthide; Water resistance